Proceedings of the 21st International Conference on Evaluation and Assessment in Software Engineering 2017
DOI: 10.1145/3084226.3084242
|View full text |Cite
|
Sign up to set email alerts
|

On the Unhappiness of Software Developers

Abstract: The happy-productive worker thesis states that happy workers are more productive. Recent research in software engineering supports the thesis, and the ideal of flourishing happiness among software developers is often expressed among industry practitioners. However, the literature suggests that a cost-effective way to foster happiness and productivity among workers could be to limit unhappiness. Psychological disorders such as job burnout and anxiety could also be reduced by limiting the negative experiences of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
62
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 67 publications
(96 reference statements)
10
62
1
2
Order By: Relevance
“…The present paper expands on these results. In addition, we have investigated the experienced causes of unhappiness (Graziotin et al, 2017b). We found that the distribution of (un)happiness among software developers, in terms of a quantitative, well established instrument for assessing happiness, pointed towards developers being a slightly happy population, with happiness scores higher than those reported for many other parts of the general human population.…”
Section: Affect and Happiness In Software Engineering Researchmentioning
confidence: 92%
See 1 more Smart Citation
“…The present paper expands on these results. In addition, we have investigated the experienced causes of unhappiness (Graziotin et al, 2017b). We found that the distribution of (un)happiness among software developers, in terms of a quantitative, well established instrument for assessing happiness, pointed towards developers being a slightly happy population, with happiness scores higher than those reported for many other parts of the general human population.…”
Section: Affect and Happiness In Software Engineering Researchmentioning
confidence: 92%
“…The overall research project employs a mixed research method, with elements of both quantitative and qualitative research (Creswell, 2009). The project aims to provide a strong, empirically based assessment of the happiness and unhappiness (Graziotin et al, 2017b) of software developers, the causes and consequences of their happiness, and the causes and consequences (Graziotin et al, 2017a,d) of their unhappiness. That is, all studies share the same general theme and use the same data sample, but have different scopes, variables, and designs.…”
Section: Methodsmentioning
confidence: 99%
“…". Cost estimation, cost models, simulation and project escalation: Madnick 1989, 1990;Basten and Mellis 2011;Cao et al 2010;Costello 1984;Houston et al 2001;Jeffery 1987;Lee et al 2012;Miranda and Abran 2008;Mukhopadhyay and Kekre 1992;Nan et al 2003;Nan and Harter 2009;Pfahl 2001;Powell et al 1999;Rahmandad and Weiss 2009;Reichelt and Lyneis 1999;Ruiz et al 2001;Yang et al 2008;Zhang et al 2006 [Borg 2014;Clegg et al 1996;Fujigaki 1996;Fujigaki and Mori 1997;Jemielniak 2009;Perlow 1998Perlow , 1999Perlow , 2001Sawyer and Southwick 2002;Staudenmayer et al 2002 Well-being [Fujigaki 1996;Fujigaki and Mori 1997;Graziotin et al 2017;Laanti 2013;Tuomivaara et al 2017] In further work, Ebert and Jones [2009] noted that projects with higher defect removal effectiveness tend to have shorter schedules, as testing is the part of development where delays typically happen. This observation is supported by Table 4 that showed a high number of papers in the quality assurance phase.…”
Section: Causes Of Time Pressurementioning
confidence: 99%
“…Time pressure was mentioned as the second most frequent reason for unhappiness among software developers in a survey conducted by Graziotin et al [2017]. Additionally, time pressure was the most frequent cause of unhappiness from factors external to the developer.…”
Section: Effect On Individualsmentioning
confidence: 99%
“…Graziotin et al (2014a) reported the results of an investigation into the relationship between the affective states and analytical problem-solving skills of software developers showing that "happy developers were better problem solvers in terms of their analytical abilities"; this stressed the importance of the psychological condition of software developers. In a recent study, Graziotin et al (2017) conducted a survey for measuring developer happiness, demonstrating that software developers are not a happy population. The authors identified factors representing causes of unhappiness for developers and highlighted the importance of considering social factors (e.g., happiness) in studies related to both human and technical aspects of software engineering.…”
Section: Affect Emotions Sentiment Analysis and Developer Personalimentioning
confidence: 99%